SDHB-Associated Paraganglioma in a Pediatric Patient and Literature Review on Hereditary Pheochromocytoma-Paraganglioma Syndromes - Heather Choat; Kerri Derrevere; Lisa Knight; Whitney Brown; Elizabeth H. Mack (Case Reports in Endocrinology)
Pheochromocytoma and paraganglioma are rare in the pediatric population occurring in approximately 1 in 50,000 children. While some cases are sporadic, they have commonly been associated with syndromes such as von Hippel-Lindau, multiple endocrine neoplasia types IIa and IIb, neurofibromatosis type 1, and hereditary pheochromocytoma-paraganglioma syndromes. In children less than 18 years of age approximately 60% of pheochromocytomas and paragangliomas are associated with a germline mutation. We present an 11-year-old child with an abdominal paraganglioma related to a succinate dehydrogenase subunit B gene mutation whose father had a previously resected abdominal paraganglioma and was found to carry the same mutation. In addition, we review the etiology, genetics, diagnostic approach, and challenges of preoperative management of secretory pheochromocytomas and paragangliomas in children.